2018
DOI: 10.3390/en11113045
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of CO2 and n-Octane in Solubility Process and α-Quartz Nanoslit

Abstract: After primary and secondary oil recovery, CO 2 -enhanced oil recovery (EOR) has become one of the most mentioned technologies in tertiary oil recovery. Since the oil is confined in an unconventional reservoir, the interfacial properties of CO 2 and oil are different from in conventional reservoirs, and play a key role in CO 2 EOR. In this study, molecular dynamics simulations are performed to investigate the interfacial properties, such as interfacial tension, minimum miscibility pressure (MMP), and CO 2 solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…On silica, CO 2 yields an angle of ∼75° to the surface. A similar orientation of CO 2 has been previously reported on silica . For muscovite and MgO, in the models considered here, CO 2 lays parallel to the surface.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…On silica, CO 2 yields an angle of ∼75° to the surface. A similar orientation of CO 2 has been previously reported on silica . For muscovite and MgO, in the models considered here, CO 2 lays parallel to the surface.…”
Section: Resultssupporting
confidence: 88%
“…A similar orientation of CO2 has been previously reported for silica. 23 For muscovite and MgO, in the models considered here, CO2 lays parallel to the surface. On the other hand, H2S on muscovite is almost in 2-hydrogen down orientation, while on silica and MgO its orientation seems to be with either one hydrogen towards the surface or parallel to it.…”
Section: Orientation Of Adsorbed Gases In the First Adsorbed Layermentioning
confidence: 96%
See 1 more Smart Citation
“…Liquid hydrocarbon (octane) static properties within quartz nanopores were explored by molecular dynamics (MD) simulations, which observed the layering structure of confined octane and concluded that the octane properties (e.g., density, self-diffusion coefficient, and viscosity) have a tendency to be bulk-liquid-like in the center of slits having apertures greater than 3.6 nm in size. Molecular simulations of CO 2 and oil mixtures in quartz, organic matter, silica, , and calcite nanoslits have been performed to investigate their structural and dynamical properties. Le et al have studied the competitive adsorption and diffusion of mixtures containing n -octane and CO 2 confined in slit-shaped silica and found that CO 2 preferential adsorption to the pore surface is likely to attenuate the surface adsorption of n -octane, lower the activation energy for n -octane diffusivity, and consequently enhance n -octane mobility at low CO 2 loading.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted for CO 2 -hydrocarbon systems confined in inorganic [13][14][15][16][17][18][19][20][21] and carbon nanopores [7,12,[22][23][24][25]. Yuan et al [23] performed MD simulations to study methane (CH 4 ) and CO 2 in carbon nanopores and found that CO 2 is more strongly adsorbed on graphite than CH 4 , resulting in CO 2 displacing CH 4 from the graphite surface.…”
Section: Introductionmentioning
confidence: 99%